Salivary and serum oxidative stress biomarkers and advanced glycation end products in periodontitis patients with or without diabetes: A cross‐sectional study. Issue 9 (4th January 2021) - Altıngöz, Sema Merve; Kurgan, Şivge; Önder, Canan; Serdar, Muhittin A.; Ünlütürk, Uğur; Uyanık, Metin; Başkal, Nilgün; Tatakis, Dimitris N.; Günhan, Meral
Abstract: Background: Non‐invasive methods for periodontitis diagnosis would be a clinically important tool. This cross‐sectional study aimed to investigate the association between oxidative stress, glycation, and inflammation markers and periodontal clinical parameters in periodontitis and periodontally healthy patients with type 2 diabetes and corresponding systemically healthy controls. Methods: Sixty‐seven periodontally healthy (DM‐H, n = 32) and periodontitis (DM‐P, n = 35) patients with type 2 diabetes, and 54 systemically healthy periodontitis (H‐P, n = 26) and periodontally healthy (H‐H, n = 28) controls were included. Clinical periodontal parameters, body mass index, fasting glucose, hemoglobin A1c (HbA1c), along with saliva and serum 8‐hydroxy‐2′‐deoxyguanosine (8‐OHdG), malondialdehyde (MDA), 4‐hydroxy‐2‐nonenal (4‐HNE), advanced glycation end products (AGE), AGE receptor (RAGE) and high sensitivity C‐reactive protein (hsCRP) levels were recorded and analyzed. Results: Salivary 8‐OHdG levels were significantly higher in periodontitis compared to periodontally healthy patients, regardless of systemic status ( P < 0.001). Salivary MDA levels were significantly higher in all disease groups compared to H‐H group ( P ≤ 0.004). Serum AGE levels were significantly higher in diabetic groups than systemically healthy groups ( P < 0.001) and in H‐ P compared to H‐H ( P < 0.001). Bleeding on probing (BOP) and clinical attachment level (CAL) strongly correlated with salivary 8‐OHdG and serum hsCRP ( P < 0.001). In systemically healthy patients, salivary 8‐OHdG was the most accurate marker to differentiate periodontitis from controls (AUC = 0.84). In diabetics salivary 4‐HNE and RAGE were the most accurate (AUC = 0.85 for both). Conclusion: Salivary 8‐OHdG alone or in combination with 4‐HNE, AGE and RAGE for diabetics, and salivary 8‐OHdG alone or in combination with MDA and hsCRP for systemically healthy persons, could potentially serve as non‐invasive screening marker(s) of periodontitis.